INDONESIAN ECONOMIC DIPLOMACY IN ACCELERATING INDONESIA-CANADA CEPA NEGOTIATIONS - Bahri, Syaiful (Moestopo International Review on Social, Humanities, and Sciences, 2024)
This research investigates the economic cooperation between Indonesia and Canada under the comprehensive economic agreement, which builds on a trade relationship established in 1951. The agreement aims to address trade challenges and boost economic activities between the two nations by incorporating economic, environmental, and human resource considerations, aligned with their national interests and values. Findings indicate that both countries are collaboratively overcoming trade barriers through comprehensive economic cooperation. Negotiations have advanced to the eighth round, addressing various sustainable issues and resulting in notable improvements in trade regulations, technical implementation, and overall cooperation. This research employs an exploratory qualitative method, focusing on bilateral cooperation and economic diplomacy. The aim is to examine and comprehend Indonesia's efforts at economic diplomacy in expediting the agreement negotiations, as well as to evaluate the effects of these initiatives on the bilateral economic ties between Canada and Indonesia, and the consequences for Indonesia's economic growth and global trade.